Effects of "Bacterfree Hand Intervention" on the knowledge, attitude of handwashing and its technique, among pre-schoolers in Wilayah Persekutuan, Malaysia - Mohamed, NA; Ridzuwan, MHM; Ungah, NAE; Jamaluddin, TZMT (Ibn Sina Trust, 2024)
Indexed by WOS/SCOPUS